The Effect of Audiovisual Media on the Speaking Ability of Children Aged 5-6 Years - Suryani, Lanny; Sit, Masganti (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Speaking ability is a vital component of early childhood language development and plays a significant role in shaping subsequent literacy skills. This study aims to examine the effect of using audiovisual learning media on the speaking ability of children aged 5-6 years at Rahmatul Iman II Kindergarten. The research employed a quantitative approach with a quasi-experimental design, specifically a non-equivalent posttest-only control group design. The sample consisted of 20 children divided into control and experimental groups. Data were collected through structured observation using a rubric of speaking ability indicators, including fluency, confidence, sentence formation, intonation, and expression. Statistical analysis revealed a significant difference between the experimental and control groups after the intervention, with the experimental group achieving a higher average posttest score. Normality and homogeneity tests confirmed that the data were normally distributed and homogeneous. Furthermore, the independent t-test indicated a statistically significant result (p < 0.05), demonstrating a positive influence of audiovisual media on children's speaking ability. These findings suggest that audiovisual media is an effective and engaging instructional strategy for enhancing young children's speaking skills and can serve as an innovative pedagogical tool for fostering language development in early childhood education.